Bibliometric Analysis of Digital Loyalty Programs - Loso Judijanto; Muhamad Ammar Muhtadi; Sintia Permata Sari (West Science Social and Humanities Studies, 2026)
Digital loyalty programs have emerged as an essential aspect of customer relationship management that helps firms build retention capabilities and sustain competitive advantage in volatile digital markets. In this study, an attempt is made to conduct a bibliometric analysis to investigate the intellectual structure, research trends, key contributors, and emerging themes in digital loyalty program scholarship. The data were collected from the Scopus database using keywords "digital loyalty program" and "customer loyalty" and analyzed using VOSviewer to conduct co-occurrence analysis, citation analysis, co-authorship analysis, institutional collaboration analysis, and country collaboration mapping. The results show that customer loyalty, customer satisfaction, and loyalty program are core themes linked with digital marketing, electronic commerce, artificial intelligence, blockchain technology, and gamification. Based on citation analysis, key theories such as blockchain-enabled trust mechanisms, AI-powered personalization, and customer experience management significantly influence the field. The collaboration analysis demonstrates that the United States, India, Indonesia, and the United Kingdom serve as major contributors to the global research network supported by influential scholars and academic institutions. Furthermore, thematic evolution indicates a transition from traditional customer relationship management perspectives toward contemporary approaches emphasizing blockchain, artificial intelligence, and gamification-based ecosystems. This study contributes by providing comprehensive mapping of digital loyalty research development and identifying critical research gaps for future scholarship, particularly in integrating emerging technologies with customer value creation.